Izmenenie pokazatelej silovoj podgotovlennosti u junych volejbolistov v processe obšcej fiziceskoj podgotovki - Gavrilova, L. G.; Saburkina, O. A.; Ovcharov, V. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
One of the most popular sports that began to develop in our country at the beginning of the last century and currently has won the universal recognition and love of many thousands of fans is volleyball. Attracting children aged 11-12 years makes it possible to conduct the process of teaching elements of the volleyball technique most effectively, which is confirmed by the scientific research and finds its application in the practice of sports training. Based on these studies, the preparatory groups of children aged 9-10 years old are recruited in the Children's and Youth Sports School in order to prepare the physical base for training the high-class athletes and general recovery of the younger generation.